2020
DOI: 10.1186/s12864-020-06853-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrative expression network analysis of microRNA and gene isoforms in sacred lotus

Abstract: Background: Gene expression is complex and regulated by multiple molecular mechanisms, such as miRNAmediated gene inhibition and alternative-splicing of pre-mRNAs. However, the coordination of interaction between miRNAs with different splicing isoforms, and the change of splicing isoform in response to different cellular environments are largely unexplored in plants. In this study, we analyzed the miRNA and mRNA transcriptome from lotus (Nelumbo nucifera), an economically important flowering plant. Results: Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…In previous studies, 11 homeotic MADS-box genes, one AP2 gene and 31 methylation region-associated genes involved in stamen petaloid in lotus have been identified (Lin et al, 2018(Lin et al, , 2019. Moreover, miR172, as a negative regulator, was also important during the crucial early stages of stamen development in lotus (Zhang Y. et al, 2020). However, the 16 candidate genes responsible for stamen petaloid variations in our study do not belong to the MADS-box family.…”
Section: Molecular Mechanisms Underlying Stamen Petaloid Formationmentioning
confidence: 50%
See 2 more Smart Citations
“…In previous studies, 11 homeotic MADS-box genes, one AP2 gene and 31 methylation region-associated genes involved in stamen petaloid in lotus have been identified (Lin et al, 2018(Lin et al, , 2019. Moreover, miR172, as a negative regulator, was also important during the crucial early stages of stamen development in lotus (Zhang Y. et al, 2020). However, the 16 candidate genes responsible for stamen petaloid variations in our study do not belong to the MADS-box family.…”
Section: Molecular Mechanisms Underlying Stamen Petaloid Formationmentioning
confidence: 50%
“…A total of 54 genes located in 14 LD blocks that have known regulatory functions in the synthesis and transport of some proteins, cellular structure and jasmonate synthesis might be involved in the control of plant size in the development of lotus (Supplementary Figure S3J; Supplementary Table S4). CLE26 (Nn4g22977), ALA3 (Nn4g22982) and VEL1 (Nn8g40603) were significantly associated with plant size variations involved in the regulation of cell differentiation in the phloem of roots and stems during auxin polar transport, vesicle-mediated transportation and the transition of the meristem from vegetative to reproductive phases (Supplementary Table S4; Kim and Sung, 2010;Czyzewicz and De Smet, 2016;Zhang X. et al, 2020). The CLE26, ALA3 and VEL1 genes were expressed primarily in the root apical meristem, immature stamen and root, respectively (Supplementary Figure S5G).…”
Section: Candidate Genes Associated With Plant Size Variationsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 F, Table S3 ). Because our previous studies suggested that transposable elements (TEs) are an important source to give birth to novel miRNAs, particularly 24 nt miRNAs [ 34 ], the difference in TE activities between five wild lotuses might be associated with these novel 24nt miRNAs. There were 437, 343, 270, 210, and 186 circRNAs found in rhizomes from China, India, Russia, Australia, and Thailand lotus, while 52 high-quality circRNAs were detected in all five samples ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have indicated that most of the essential miRNAs for biological processes target TFs or stress-response factors. In the absence of miRNAs and their regulation, plants would suffer developmental deficiencies in many critical developmental stages [ 73 , 74 ].…”
Section: Further Regulatory Genes Potentially Contributing To Multica...mentioning
confidence: 99%